2014
DOI: 10.5455/medarh.2014.68.90-93
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fibrin Glue Polypropylene Mesh Fixation in Open Inguinal Hernia Repair

Abstract: The aim:of this study was to compare two methods of polypropylene mesh fixation for inguinal hernia repair according to Lichtenstein using fibrin glue and suture fixation.Material and Methods:The study included 60 patients with unilateral inguinal hernia, divided into two groups of 30 patients – Suture fixation and fibrin glue fixation.All patients were analyzed according to:age, gender, body mass index (BMI), indication for surgery–the type, localization and size of the hernia, preoperative level of pain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Cyanoacrylates were the first of such adhesives to be investigated. They have shown quick tissue adhesion and are practical to use [5][6][7][8]. Other types of sealants have also been used, such as sealants derived from human blood, which present risks such as embolization, infection, and parvovirus B19 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cyanoacrylates were the first of such adhesives to be investigated. They have shown quick tissue adhesion and are practical to use [5][6][7][8]. Other types of sealants have also been used, such as sealants derived from human blood, which present risks such as embolization, infection, and parvovirus B19 [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Study conducted by Amerodobasic et al showed to hematoma formation in both study and control group, similarly another study conducted by Girish et a in 2016 showed that 7% patients in control group and 4% patients in study group developed haematoma, which was statistically not significant. 14,16 Our study showed that 7 patients among prolene group and 3 patients in fibrin glue group had developed haematoma in early post-operative period and this finding was statistically in-significant with a p>0.05, suggesting that haematoma formation is seen in both types of mesh fixation.…”
Section: Discussionmentioning
confidence: 60%
“…This was similar to other studies like AmerOdobasic et al and Testini et al, suggesting that inguinal hernias are predominant in male population. 14,15 The observations of Girish et al were 56% of the total inguinal hernias were right sided, 38% were left sided. 16 Paajanen et al evaluated inguinal hernias and found that 54.3% were right sided, 45.7% were left sided.…”
Section: Discussionmentioning
confidence: 98%
“…Lower NRS pain score at seven days and one year compared to sutures [1]. Lower VAS pain score at one day, seven days, and one month compared to sutures [5]. 5.9%…”
Section: Painmentioning
confidence: 99%